Design, fabrication and modelling of four-wheeled mobile robot platform with two differential and two caster wheels - M. Sawal, A. R.; Ali, Mohammed A. H.; Sha’akmal, S.; A. Azwan, A. R. (Universiti Malaysia Pahang, 2018)
This paper presents a design and modeling of wheeled mobile robot (MWR) when navigating autonomously in environment such as road and factory. It needs a good and robust design and control for wheeled mobile robot to move from one to another points with smooth moving and small tracking errors. This paper is focused on mechanical design and modeling of wheeled mobile robot. Autodesk inventor software is used to draw the design of the WMR because this software is simple to make any design and a wheeled mobile robot structure is designed with a center of gravity to be located below the axle wheels level. The wheeled mobile robot is driven using two differential drive and two castor wheels to balance robot while it is moving in the environment. Two kinds of coordinate systems are used to describe the movement of the robot in the environment; namely are Local and global coordinate system; where local is related to the heading angle and the deferential wheel shaft, however the global describes the motion in x, y and z directions. The kinematic model is derived for the four wheeled mobile robot using angular velocities equations for the left and right wheels with estimation the heading angle of the robot.